Investigating self-beliefs and success for English medium instruction learners studying finance - Thompson, G; Takezawa, N; Rose, H (Taylor and Francis, 2021)
English is increasingly being used as a medium instruction in business education at the tertiary level, with its growth fuelled by university internationalization. As a result, many students enrolled in English medium business programs are learning through a second or foreign language, with variant levels of prior knowledge and experiences. This raises questions over the impact these factors have on students’ ability to succeed. This paper reports on an investigation of the extent that English language proficiency, mathematical ability, English self-efficacy, mathematical selfefficacy, experience overseas, and gender predict success in studying finance in English at a university in Japan.